Functionalized acrylic polyhydroxy urethanes as molecular tool box for photocurable thermosets and 3D printing. Issue 10 (24th March 2021) - Buchheit, Hannah; Bruchmann, Bernd; Stoll, Klaus; Mülhaupt, Rolf
Abstract: Liquid urethane (meth)acrylates represent attractive components of photocurable thermosets for applications ranging from coatings and adhesives to 3D printing. Herein we tailor liquid polyfunctional urethane methacrylates (UMA) derived from acrylic polyhydroxy urethanes. Cyclic carbonate methacrylates react with diamines to form dihydroxy‐functional urethane dimethacrylates. In an "one‐pot" process the hydroxy groups are functionalized either by reaction with 2‐isocyanatoethyl methacrylate (IEMA) or by esterification with methacrylic anhydride (MAA) and acetic anhydride (AA). The hydroxy group esterification substantially lowers the resin viscosity (26–156 Pas). Hydroxy functionalization with IEMA and MAA affords tetrafunctional methacrylates. The corresponding photo‐cured thermosets exhibit higher crosslinking density and improved stiffness as reflected by increasing the Young's modulus from 2900 to 3700 MPa combined with increasing the glass temperature from 135 to 204°C. Hence, this facile molecular UMA design enables to control functionality and thermoset properties over a wide range and meets the demands of 3D printing applications. Abstract :